The Legal Analysis Related to Compensation in Land Procurement for the Construction of the Semarang-Demak Toll Road - Kencana, Dyah Ayu Manggar; Riyanto, Taufan Fajar (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
The land has a vital function in this country, this is because in one dimension land has the function of fulfilling the needs of human life personally and in another dimension land also has a social function to meet the needs of national development. The social dimension of land creates a system of compensation for every individual in society whose land is affected by land acquisition for development in the public interest. The implementation of compensation within the framework of land acquisition for development for the public interest has in fact not met the expectations of the community, especially in the Semarang-Demak toll road construction project. This article examines the issue of compensation in the procurement of land for the construction of the Semarang-Demak toll road, which is still far from the expectations of the community. The method used in this paper is normative juridical. Keywords: Acquisition; Compensation; Land.